2021
DOI: 10.3389/fonc.2020.603671
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling and Prognostic Value Analysis of Genetic Alterations in Chinese Resected Lung Cancer With Invasive Mucinous Adenocarcinoma

Abstract: BackgroundInvasive mucinous adenocarcinoma (IMA) of the lung is a distinct histological subtype with unique clinical and pathological features. Despite previous genomic studies on lung IMA, the genetic characteristics and the prognosis-related biomarkers in Chinese surgically resected lung IMA remain unclear.MethodsWe collected 76 surgically resected primary tumors of invasive lung adenocarcinoma, including 51 IMA and 25 non-mucinous adenocarcinomas (non-IMA). IMA was further divided into pure-IMA (mucinous fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…IMA is regarded as a distinct pathological type of LUAD based on its unique clinical and genetic features (17). However, while there have been many studies on the prognosis of pulmonary IMA, the conclusions among these studies have been highly contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…IMA is regarded as a distinct pathological type of LUAD based on its unique clinical and genetic features (17). However, while there have been many studies on the prognosis of pulmonary IMA, the conclusions among these studies have been highly contradictory.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this difference, the RFS and OS results were different from those of previous studies. The clinical outcome of IMA has been controversial 10,23,30,31 due to its low incidence, which is approximately 1.5% of total lung cancers. 27 Lee et al reported a relatively favorable prognosis of IMA and that it was better than acinar or papillary predominant type INMA in disease-free survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of advanced cancer, adjuvant therapy is performed according to genetic alterations, such as EGFR, ALK, ROS, and KRAS mutations. In the case of IMA, there is almost no EGFR mutation, 31 , 43 , 44 , 45 therefore tyrosine kinase inhibitors (TKIs) are not used, affecting survival. Due to these differences in adjuvant treatments, we believe that RFS is a better assessment tool for comparing clinical prognosis in various histologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the present study, 16.1% of IMA patients have EGFR mutations and 29.0% with ALK rearrangement, which was consistent with previous studies indicating that IMA patients have a lower frequency of EGFR mutations and a higher frequency of ALK rearrangements than non-IMA patients ( 8 , 9 , 12 ). Our former next-generation sequencing (NGS)-based study using a panel of 425 genes has identified that KRAS mutations were the most frequent oncogenic driver mutations in IMAs (23.1% in pure-IMA group and 4.0% in mixed-IMA group) ( 22 ). However, owing to the rarity or absence of targetable mutations, there are few studies on the target therapy of IMA ( 23 ).…”
Section: Discussionmentioning
confidence: 99%